Assessment of students’ metacognitive skills in the context of education 4.0 - Popandopulo, Anar; Kudysheva, Ainash; Fominykh, Nataliia; Nurgaliyeva, Murshida; Kudarova, Nazgul (Frontiers in Education, 2023)
Introduction This article measures the meta-comprehension of reading practices among schoolchildren and students. Methods The Metacognitive Awareness of Reading Strategies Inventory (MARSI) and Metacognitive Awareness of Reading Strategies Scale (MAI) was used to do this. Results The research results showed that MARSI students overall outperformed MARSI high school students, and the differences were tested using Student’s t-test. The problem-solving subscale recorded high levels for students and moderate levels for high school students. Supported reading strategies and Global reading strategies were in the medium range for each age group. Discussion The obtained results are primarily important for students and teachers. By being aware of their cognitive processes, students take the first step towards meaningful and thoughtful reading, which is the goal of many modern developments and approaches. As students become more aware of their cognitive processes, their role in the learning process expands to the point where they dominate it, rather than the teacher.